From history of moral culture toward applied ethics: T. G. Abolina's ethical researches at Kyiv university - Rohozha, Mariya; Panchenko, Valentyna (Ukrainian Cultural Studies, 2022)
The article is focused on the academic legacy of Tetyana G. Abolina (1950–2015), doctor of philosophical sciences, professor of Taras Shevchenko National University of Kyiv. Ethics as the science paved the way with difficulties at domestic academic environment in the mid of the previous century. It has been transforming from the marxist-leninist propaganda toward moral theory. The ability of a professional ethicist to find one's own path in the field and create personal intellectual niche for academic activity testified the uprise of the worthy of attention theorist. Thus, the 'star' of T. G. Abolina had flared. For 37 years at the University Department of Ethics, Aesthetics and Culture Studies she had come the path from marxist-leninist ethics primarily toward research of history of moral culture in the context of socio-cultural dynamics. Moral culture was comprehended by prof. T. G. Abolina as the system of person's self-affirmation which possessed internal structure and was changing at every level of cultural-historical process in its main and specific characteristics and definite historical forms. Moral culture was understood in integrity of all aspects of practical reason, exposed specifics of historical forms, their internal structure and natural integrity. Last fifteen years of her life, prof. T. G. Abolina came to the theory of applied ethics and ethical expertise in definite fields of social life. She considered applied ethics as the procedure of morally-ethical thinking that is the natural synthesis of theory and practice, immediate usage of theory in practice. The article pays attention to Abolina's understanding of ethical expertise of social projects and practical potentiality of ethical projects in the field of public philosophy as well as ethics application to social practice and her personal 'applied turn' and activities she initiated at that way. The paper deals with the analysis of her personal monograph "Historical Destiny of Morality. Philosophical Analysis of Moral Culture" (1992), her PhD (1982) and doctoral (1999) dissertations. Prof. T. G. Abolina delivered special courses at the faculty of philosophy, which reflected her academic search at each period of time. Main ideas of her courses "Ideas of the New Ethics in the Spiritual Culture of the 20th Century" and "Evil and Fiction" are analyzed in the article.
Keywords: T. G. Abolina; ethics; history of moral culture; communication – separation; applied ethics; ethical expertise